2016
DOI: 10.1177/1358863x15623629
|View full text |Cite
|
Sign up to set email alerts
|

The association between ischemic and jeopardized myocardia and all-cause mortality in patients with peripheral artery disease

Abstract: Peripheral artery disease (PAD) is associated with increased mortality and concomitant coronary artery disease (CAD). However, it is unclear whether uncovering the presence of functional coronary ischemia by single-photon emission computed tomography (SPECT) myocardial perfusion imaging (MPI) would further help stratifying that excess risk. From January 2000 to 2009, 4294 individuals underwent cardiac stress testing within 180 days of ankle-brachial index (ABI) measurements. Of these, 645 had PAD and SPECT MPI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…1 First, they suggested that the relationship between all-cause mortality, including multiple outcome variables, and sarcopenia should be determined by hierarchical modeling analysis. [2][3][4][5] This analysis might better clarify the association between sarcopenia and all-cause mortality. Table 1 showed the analysis results based on the hierarchical Cox proportional hazards model.…”
mentioning
confidence: 99%
“…1 First, they suggested that the relationship between all-cause mortality, including multiple outcome variables, and sarcopenia should be determined by hierarchical modeling analysis. [2][3][4][5] This analysis might better clarify the association between sarcopenia and all-cause mortality. Table 1 showed the analysis results based on the hierarchical Cox proportional hazards model.…”
mentioning
confidence: 99%